Metabolomic Profile Reveals That Ceramide Metabolic Disturbance Plays an Important Role in Thoracic Aortic Dissection - Yang, Hang; Yang, Fangfang; Luo, Mingyao; Chen, Qianlong; Liu, Xuanyu; Zhang, Yinhui; Zhu, Guoyan; Chen, Wen; Li, Tianjiao; Shu, Chang; Zhou, Zhou (Frontiers in Cardiovascular Medicine, 2022)
Aims Thoracic aortic dissection (TAD) is a life-threatening disease with no effective drug therapy thus far. New therapeutic targets and indications for timely surgical intervention are urgently needed. Our aim is to investigate new pathological mechanisms and potential biomarkers of TAD through global metabolomic profiling of aortic aneurysm and dissection patients. Methods and Results We performed untargeted metabolomics to determine plasma metabolite concentrations in an aortic disease cohort, including 70 thoracic aortic aneurysm (TAA) and 70 TAD patients, as well as 70 healthy controls. Comparative analysis revealed that sphingolipid, especially its core metabolite C18-ceramide, was significantly distinguished in TAD patients but not in TAA patients, which was confirmed by subsequent quantitative analysis of C18-ceramide in a validation cohort. By analyzing our existing multiomics data in aortic tissue in a murine TAD model and TAD patients, we found that an enhanced ceramide de novo synthesis pathway in macrophages might contribute to the elevated ceramide. Inhibition of the ceramide de novo synthesis pathway by myriocin markedly alleviated BAPN-induced aortic inflammation and dissection in mice. In vitro studies demonstrated that exogenous C18-ceramide promoted macrophage inflammation and matrix metalloprotein (MMP) expression through the NLRP3-caspase 1 pathway. In contrast, inhibition of endogenous ceramide synthesis by myriocin attenuated lipopolysaccharide (LPS)-induced macrophage inflammation. Conclusions Our findings demonstrated that ceramide metabolism disturbance might play a vital role in TAD development by aggravating aortic inflammation through the NLRP3 pathway, possibly providing a new target for pharmacological therapy and a potential biomarker of TAD.